Analisis Perilaku Keagamaan Mahasiswa UIN Raden Mas Said Surakarta Pengguna Aplikasi TikTok - Reva Yuliana Nur Rohmah; Vivi Ida Mardiana; Nurul Ilmi; Nuzulul Tazkhiyatun; Rilis Wahyu Diana Nur Prajati (Academica: Journal of Multidisciplinary Studies, 2022)
The TikTok application has many users, one of which is in Indonesia. Users consist of various groups, including students. Many students have accounts and are active in using the TikTok application. The use of the TikTok application by students has various impacts on student behavior. The purpose of this study was to determine the impact of the use of TikTok on the religious behavior of students at the State University of Raden Mas Said Surakarta. The method used in this study is a qualitative method while the data obtained from interviews, observations and observations. The use of the TikTok application by UIN Raden Mas Said Surakarta students has a positive and negative impact. The positive impact is when students watch content of knowledge, education, and da'wah. While the negative impact that occurs is the behavior of delaying prayer. The majority of students access the TikTok application only to get entertainment from the content presented. Keywords: Impact; Religious Behavior; TikTok